A systematic review of case-series studies on the effectiveness of interventions to reduce polypharmacy and its adverse consequences in the elderly (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Aging is frequently accompanied by chronic diseases; as a consequence, older people are often exposed to polypharmacy that has been associated with negative health-consequences. The aim of this study is to conduct a systematic review of the literature reporting on the effectiveness of different approaches to reduce polypharmacy in the elderly.Methods. We conducted a comprehensive literature search of MEDLINE, Scopus and ISI Web of Knowledge databases. Eligible studies were case-series reporting outcomes of interventions aimed at reducing polypharmacy and its consequences in the elderly. A quality appraisal of the studies included was performed.Results. Nineteen studies were included, of which six conducted in community setting, seven in hospital setting, and six in nursing homes. Seventeen of them were judged as moderate quality, and two of them as poor quality. The majority of the interventions were carried out by pharmacists, alone (35%) or with other professionals (40%). Interventions consisted in pharmacotherapy reviews based on various tools and software; in some cases educational interventions were performed for review-performers and patients. Studies conducted in community-setting provided also a feedback to primary care physician. The outcomes included five categories: therapy’s characteristics (e.g. number of drugs, appropriate prescriptions), quality of life, health-related outcomes, costs, healthcare services’ utilization. Therapy-related outcomes were those more affected by all types of interventions.Conclusion. Interventions aimed at reviewing patients’ therapy are effective in optimizing the use of drugs, and could be considered also  in improving quality of life, healthcare costs, services’ utilization, and health-related outcomes.